PENGARUH EKSTRAK KULIT JERUK PURUT (CITRUS HYSTRIX DC) TERHADAP MORTALITAS KUTU DAUN PADA TANAMAN KEDELAI (GLYCINE MEX L) - Halisah Suriani (Universitas Pahlawan Tuanku Tambusai, 2022)
This studi aims to determine the effect of kaffir lime peel extract (Citrus hytrix DC) on the mortality of aphids on soybean plants (Glycine max L). This research was conducted at the laboratory of the faculty of teaching and education UGL Aceh fron August 2022. It was a nonfactorial complete randomize design experiment (CRD) with 3 replications and 5 treatments, with a sample of 75 aphids. The parameter observed was the mortality rate of aphids. Based on the research result, giving kaffir lime peel extract (Citrus hystrix DC) had a very significant effect on the mortality of aphids on soybean plants. Where is the mortality one hour after spraying Fcount = 105,22 (0,05)>Ftable = 3,48. While two hours after spraying F count = 0,74 < F table = 3,48 for a significance level of 0,01% = 5,98. From the results of data analysis showed that there was a significant effect on the percentage of pahids mortality on soybean plants. This can be seen freom the results of the analysisof variance (ANAVA) where Fcount > Ftable, then Ha is accepted. Keywords: lime peel extract, mortality, aphids, soybean plants